The socio-historical basis of the problem of ontology in philosophy (Journal of Philosophy Culture and Political Science, 2018)
The article analyzes the socio-historical basis and specificity of metamorphosis ontological perspective philosophical worldview. Uncovered historical and spiritual features, the mechanisms of transformation and the meaning of «structure of the universe», «existence», «movement», «Logo», «NUS». Identify the values that serve as the standard of truth, promises and causes of ontological inquiry in the age of the crisis of the postmodern.Key words: Genesis, the boundaries of knowledge, philosophical reflection, advocates of labor, the absolute spirit, truth, destiny, necessity, ontological nihilism, the essence of the soul, transcendence